Missed initial appointments at Israeli child development centres: Rate, reasons, and associated characteristics. (16th June 2022) - Hirsh‐Yechezkel, Galit; Glasser, Saralee; Gabis, Lidia V.; Eden, Avi; Savitzki, David; Farhi, Adel; Luxenburg, Osnat; Levitan, Gila; Lerner‐Geva, Liat
Abstract: Introduction: Missed appointments (MAs) at child development centres (ChDCs) cause multiple problems: they preclude timely diagnosis and treatment of both the invited child and children whose appointment was delayed due to overbooking, as well as disrupting efficient organisational management. The aim of this study was to assess the rate and describe the reasons for missed appointments at Israeli ChDCs, and to evaluate the association of socio‐demographic, clinical, and administrative variables with MA rates. Methods: This nested case‐control study included all children scheduled for initial appointments ( N = 1143) at three centres during 1 year. Parents of children who missed their appointment and a sample of those who attended were interviewed by telephone. Results: The rate of missed appointments was 26.6%, and the most frequent reasons were unexpected events (26.0%) and lack of insurance coverage (23.4%). Variables associated with lower MA rates were: having had ≥3 types of rehabilitative interventions (odds ratios (OR) = 0.26; 95% confidence interval [CI] 0.16–0.44), detailed referral letter (OR = 0.48; 95%CI 0.30–0.75), telephone reminder (OR = 0.37; 95%CI 0.24–0.57) and health maintenance organisations or private insurance coverage (OR = 0.12; 95%CI 0.06–0.17 and OR = 0.56; 95% CI 0.38–0.89, respectively). Conclusion: Encouraging physician's referral letters and personal‐contact reminders can reduce missed appointments. Understanding the family's and the child's personal characteristics, and the organisational/administrative aspects of missed appointments may guide efforts to ensure timely care for every child. Highlights: The missed appointment (MA) rate at Child Development Centres (ChDCs) was 26.6% The most frequent reasons was unexpected personal events, for example, child's illness Children who had received previous rehabilitative therapy had lower MA rates Organisational factors, for example, insurance, reminders, were associated with MA rates